Electronic structure of materials - Prasad, Rajendra (Boca Raton : CRC Press, 2014)
"This book is a compilation of lecture notes from a course on the electronic structure of materials targeted at students in physics and materials science. The book covers the fundamentals of electronic structure, methods to calculate the electronic structure of solids, calculation of some properties, and some applications. It presents the fundamentals of electronic structure and its important applications to a wide variety of materials with emphasis on materials of current interest. This book shows how materials can be understood based on the basic principles of physics. Some basic knowledge of quantum mechanics, statistical mechanics, and condensed matter physics is recommended"--
Includes bibliographical references and index
Keywords: Electronic structure; Materials -- Electric properties; Electronic apparatus and appliances -- Materials